Reducing Inbound Warehouse Operation Waste Through Lean Manufacturing: A Case Study of Small and Medium Enterprises (SME) - Putu Aulia Pranagita; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2023)
A third-party producer, Company A, partners with a multinational corporation to package and transport the finished goods produced for its customers. To meet customer demand, Company A must maintain a considerably low lead time and an adequate level of inventory. To reduce lead times and non-value-added (NVA) activity times the warehouse operations, especially in inbound processes at an SME Manufacturing Facility, this research intends to analyze the impact of implementing lean manufacturing. Lead time and NVA time for the current operation are 9045 minutes and 275 minutes, respectively. Value stream mapping (VSM) is selected as the tool to identify process waste and launch an improvement strategy to achieve the research objective. The creation of the current state mapping and evaluation of the future state mapping will be the first steps in the implementation approaches. The proposed improvements include creating and implementing a VBA application as a data entry form for supplier shipment booking, an information system for material reception, an operational report, and remodeling the staging area by incorporating a gravity roller. The lead time is decreased by 5% as the improvement strategy is put into action, while the NVA time is dramatically decreased by 47.27%.  The research conclusions are thus recognized as noteworthy and beneficial in advancing the understanding of the role of value stream mapping methods in improving inbound warehouse performance in SMEs.